2013
DOI: 10.1109/tvcg.2013.125
|View full text |Cite
|
Sign up to set email alerts
|

A Partition-Based Framework for Building and Validating Regression Models

Abstract: Regression models play a key role in many application domains for analyzing or predicting a quantitative dependent variable based on one or more independent variables. Automated approaches for building regression models are typically limited with respect to incorporating domain knowledge in the process of selecting input variables (also known as feature subset selection). Other limitations include the identification of local structures, transformations, and interactions between variables. The contribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 37 publications
0
105
0
Order By: Relevance
“…The authors observed that a visualization-powered approach not only speeds up model building process but also increases the trust and confidence in the results. Mühlbacher and Piringer [13] discuss how the process of building regression models can benefit from integrating domain knowledge. Berger et al [14] introduce an interactive approach to inspect the parameter space in comparison to multiple target values.…”
Section: Related Workmentioning
confidence: 99%
“…The authors observed that a visualization-powered approach not only speeds up model building process but also increases the trust and confidence in the results. Mühlbacher and Piringer [13] discuss how the process of building regression models can benefit from integrating domain knowledge. Berger et al [14] introduce an interactive approach to inspect the parameter space in comparison to multiple target values.…”
Section: Related Workmentioning
confidence: 99%
“…A classifier may be built for assigning new objects to previously obtained clusters [3] [26]. Visual analytics techniques also support derivation of linear trend models from multivariate data [32], regression models [51], and time series models [13] [34]. Other works focus on supporting assessment of existing models, including classification [49], engineering simulation [47] [48], and spatio-temporal models [21][46] [55].…”
Section: Visual Analytics Support To Modeling and Simulationmentioning
confidence: 99%
“…[51], [52], [53], [54], [55], [56] Groups & Classification [57] [58], [59] [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74] [75], [76], [77], [78], [79], [80] Dependence & Prediction [81], [82], [46] [83], [84], [85], [86], [87], [88], [89] [90], [91], [92] being analyzed. The results are then presented to the user through different visual encodings that are often accompanied by interaction.…”
Section: Levels Of Integrationmentioning
confidence: 99%
“…Mühlbacher and Piringer [85] (see Figure 6) discuss how the process of building regression models can benefit from integrating domain knowledge. In the framework called Vismon, visualization has helped analysts to make predictions and investigate the uncertainties that are existent in relations within simulation parameters [86] (see Figure 5).…”
Section: Semi Interactive Visualizationmentioning
confidence: 99%